2016
DOI: 10.3906/sag-1405-72
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and their relation with clinical parametersand androgen levels in hirsute women

Abstract: Background/aim: The purpose of this study was to assess the prevalence of anxiety and depression among patients with hirsutism and to evaluate the relationships of anxiety and depression with clinical parameters and androgen levels. Materials and methods:One hundred and seven women with hirsutism were enrolled in the study. All participants completed standardized questionnaires to assess depression (Beck Depression Inventory (BDI)) and anxiety (Beck Anxiety Inventory (BAI)). The Ferriman-Gallwey (FG) scores, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Weber showed that correlation of serum testosterone is significant only in women with severe depression ( 23 ). Depression and the severity of depressive symptoms were positively correlated with dehydroepiandrosterone sulfate levels, not testosterone levels in an IRAK study ( 8 ). Hypothalamic-pituitary adrenal system dysregulation has an important role in the pathophysiology of depression that is reflected by an increased secretion of adrenal hormones, especially cortisol and dehydroepiandrosterone ( 23 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Weber showed that correlation of serum testosterone is significant only in women with severe depression ( 23 ). Depression and the severity of depressive symptoms were positively correlated with dehydroepiandrosterone sulfate levels, not testosterone levels in an IRAK study ( 8 ). Hypothalamic-pituitary adrenal system dysregulation has an important role in the pathophysiology of depression that is reflected by an increased secretion of adrenal hormones, especially cortisol and dehydroepiandrosterone ( 23 ).…”
Section: Discussionmentioning
confidence: 96%
“…Also, regular exercise and using drugs such as metformin may be a potential confounder of the relationship between depression and insulin resistance that were neglected in our study. Association between depression and testosterone level has been evaluated in several studies with conflicting results ( 6 , 8 , 10 , 17 ). In the present study, there is no correlation between testosterone level and depression in PCOS and non-PCOS women and all of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is defined as a type of mood illness characterized by a persistent sense of sadness and lack of interest. The study showed that women are about twice as likely as males to suffer from depression [5]. In addition to that women who started using a contraceptive patch experienced roughly twice the risk of subsequently starting an antidepressant or being diagnosed with depression [6].…”
Section: Introductionmentioning
confidence: 95%
“…It can lead to a variety of psychological issues. Affected women may experience anxiety and depression (Irak et al, 2016). Hirsutism is one of the most important predictors of poor quality of life in women with PCOS (Guyatt et al, 2004;Kiran et al, 2018).…”
Section: Introductionmentioning
confidence: 99%